2020
DOI: 10.13057/biodiv/d210959
|View full text |Cite
|
Sign up to set email alerts
|

The growth of Shorea leprosula at various planting distances and slopes in Gunung Dahu Research Forest, Bogor, Indonesia

Abstract: Abstract. Pamoengkas P, Rachmat HH, Khalifa N. 2020. The growth of Shorea leprosula at various planting distances and slopes in Gunung Dahu Research Forest, Bogor, Indonesia. Biodiversitas 21: 4396-4404. Shorea leprosula Miq. is one of the species of Dipterocarpaceae family which has great potential to be developed as plantation forestry. This research aimed to investigate the effect of planting distance and slope on the growth of S. leprosula in Gunung Dahu Research Forest, Bogor, Indonesia. Growth variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In the first planting phase, pioneer plants (i.e., Melaleuca cajuputi, Cassia siamea, Acacia mangium, Acacia auriculiformis, Pterocarpus indicus, Enterolobium cyclocarpum, Adenanthera pavonina, Samanea saman, and Delonix regia) were planted with a spacing of 4x4m and 4x6m. Research by Pamoengkas et al (2020) found that 4x6m spacing resulted in better height and diameter for woody plants, S. leprosula. As for M. cajuputi (eucalyptus), a spacing of 3x3m is sufficient because it has a light canopy.…”
Section: Data Collectionmentioning
confidence: 99%
“…In the first planting phase, pioneer plants (i.e., Melaleuca cajuputi, Cassia siamea, Acacia mangium, Acacia auriculiformis, Pterocarpus indicus, Enterolobium cyclocarpum, Adenanthera pavonina, Samanea saman, and Delonix regia) were planted with a spacing of 4x4m and 4x6m. Research by Pamoengkas et al (2020) found that 4x6m spacing resulted in better height and diameter for woody plants, S. leprosula. As for M. cajuputi (eucalyptus), a spacing of 3x3m is sufficient because it has a light canopy.…”
Section: Data Collectionmentioning
confidence: 99%
“…This competition would increase in the later developmental stages, with a denser population has higher competition and affected the availability of nutrients, light, and water [50]. Different growth performances were also observed within similar dipterocarps species affected by slopes and spacing distance [44]. Table 1 shows the performance of dipterocarps species planted at the reforested landscape with various initial conditions.…”
Section: Reforestation Yields Timber Stock and Increases Forest Covermentioning
confidence: 99%
“…Planting dipterocarps for forest rehabilitation and restoration has been widely adopted in Indonesia and can be a form of ex situ conservation [43][44][45]. Dipterocarp seedlings can be planted on open grassland with high light intensity as the major limiting factor for species survival.…”
Section: Introductionmentioning
confidence: 99%
“…The highest DMAI value was showed by S. platyclados (2.1 cm year -1 ). The same species may come to different category of DMAI rate depend on planting distance and silvicultural treatment [23]. More spacious planting diatance allowed higher DMAI value.…”
Section: Good Performance Of Native Trees In the Man-made Dipterocarpmentioning
confidence: 99%
“…Slopes also affects tree growth. Different slope gradients are known to have different impact on stand performance [23]. Gentle sloping class provides better growth for both the diameter and tree height.…”
Section: Soil Characteristics Land Productivity and Potential Hydrolmentioning
confidence: 99%